OPTIMISASI SISTEM INFORMASI MANAJEMEN RUANGAN PADA WEBSITE SIPERAD MENGGUNAKAN METODE WATERFALL - Aqil Aswangga Anggaraksa; Ria Arafiyah; Carli Apriansyah Hutagalung (Universitas Negeri Jakarta, 2026)
Room reservation management at Universitas Negeri Jakarta's Dewi Sartika Building faced persistent inefficiencies in the existing SIPERAD (Sistem Informasi Peminjaman Ruangan dan Presensi Perkuliahan) platform, including manual one-by-one data entry, the absence of a data export feature, and uncertainty about whether scheduled classes were actually held, which caused rooms to remain marked as occupied although they were in fact vacant. This study aims to develop and implement a web-based room management system with an integrated automatic notification feature to confirm classroom usage and improve room utilization efficiency. The system was developed using the Waterfall method, covering requirements analysis, system design with UML and Entity Relationship Diagram modeling, backend and frontend implementation using the Laravel framework, and system testing. The developed features include automatic web push notifications sent one day before scheduled classes, a course-in-charge confirmation mechanism, bulk data import via CSV, and report export in Excel and PDF formats. Testing was carried out using Black Box Testing to verify functional requirements and User Acceptance Testing (UAT) to assess user acceptance. Black Box Testing results showed that all 31 test scenarios for the Admin role and all 5 test scenarios for the Student role produced valid outputs, indicating 100% functional validity. UAT results indicated a very high acceptance level, with satisfaction percentages of 95.79% from Admin users and 89.69% from Student users, both categorized as